A REVIEW ON THE IMPORTANCE OF PRACTICE IN LEARNING ENGLISH AS A SECOND LANGUAGE: INCLUDING BARRIERS, CONSEQUENCES, AND TECHNIQUES - Seenivasan, Suganya; Pillai, Mamta (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Learning English as a second language is essential in today’s worldwide community. However, a major challenge for many students is a lack of experience. This review examines the value of practice in language learning, its function in the development of vocabulary, grammar, and fluency, and how it relates classroom instruction to everyday interactions. Cultural hurdles, fear of making mistakes, and limited exposure to native speakers are some of the elements the author considers as contributing to the lack of practice. Consequences of this deficit include limited possibilities, slower advancement, and communication problems. To tackle these problems, we recommend language exchange programs, diversified English usage, realistic resources, digital platforms, and supportive classrooms. In order to promote practice, the author highlights the collaboration between teachers and students. To sum up, practice is crucial to learning English. The author urges collaborations to close the gap between teaching and practice, fostering an atmosphere that supports language learners.